The January Effect and Lunar New Year Influences in Frontier Markets: Evidence from the Vietnam Stock Market - Truong, Loc Dong; Friday, H. Swint (International Journal of Economics and Financial Issues, 2021)
This analysis investigates the influence of the timing of the Lunar New Year on the January effect for the Vietnam stock market. The data selected for this study is a weekly series of the market index (VN-Index) over the period from January 7th, 2009 through December 26th, 2018. To test for the presence of the January effect and the impact of timing of the Lunar New Year on the January anomaly, OLS and GARCH(1,1) regression models are employed. The empirical findings obtained from these models confirm the existence of the January effect during this period in the Vietnam stock market. However, the analysis reveals that the January effect is only in existence when the Lunar New Year is in February, but it is disappearing when the Lunar New Year falls in January. These findings suggest that Lunar New Year has a significant impact on the January anomaly in the Vietnam stock market providing evidence against tax loss selling while supporting other holiday and window dressing hypotheses for this widely documented seasonal phenomenon. Keywords: The January effect, Lunar New Year influences, Vietnam stock market JEL Classifications: G10, G40 DOI: https://doi.org/10.32479/ijefi.10928